PENERAPAN MEDIA RODA PUTAR PUZZLE PINTAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Ili, La; Handayani, Gusti; Saputra, Nanda (Jurnal Ilmiah Aquinas, 2021)
This study aims to: (1) increase student activity during the learning activities of sub-theme 1energy sources; (2) Improve learning outcomes in sub-theme 1 energy sources; and (3) Producinglearning media for sub-theme 1 sources of innovative energy that can increase motivation and learning outcomes in sub-theme 1 energy sources. This type of research is a classroom action research using the Kemmis and Mc. Taggart. This media is motivated by the students' mastery of the subject matter is low, the activity of students during the learning process is very lacking, students are less interested in the methods and media used by researchers. This innovative work consists of two types of media, namely the Spinning Wheel and the Smart Puzzle. This rotating wheel uses iron and used parabolic plates. Meanwhile, this Smart Puzzle is made from Styrofoam and Asturo paper. The wheel will stop pointing to a source of energy for the students to arrange their smart puzzles. The results obtained in the practical application of this media are that it can increase motivation and learning achievement in sub-theme 1 energy sources for fourth grade students of SDN 2 Sigli. It is proven in the first cycle of 33 students who achieved complete learning, 16 students or 48.5% obtained an average score of 68.2. Then the complete students increased again in the second cycle to 28 students or 84.9% with an average score of 77.6 which exceeded the indicator achievement target of 70. Based on the results of observations, this learning process was in a good category. .